2020
DOI: 10.21037/jtd.2020.02.27
|View full text |Cite
|
Sign up to set email alerts
|

The impact of immune-inflammation-nutritional parameters on the prognosis of non-small cell lung cancer patients treated with atezolizumab

Abstract: Background: Immunotherapy targeting programmed cell death-1 (PD-1) and programmed death-ligand 1 (PD-L1) has become the forefront strategy for systemic therapy in advanced non-small cell lung cancer (NSCLC) patients. PD-L1 expression on tumor cells has been reported as an eligible biomarker of response to such immunotherapies. However, useful biomarkers of response to atezolizumab, an anti PD-L1 antibody, are unestablished. Methods: We retrospectively analyzed clinicopathological characteristics including PD-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 27 publications
2
64
1
Order By: Relevance
“…Preoperative nutritional evaluation and support by ERAS nursing program can reduce the incidence of insulin resistance and postoperative hyperglycemia, and reduce preoperative anxiety. The improvement of nutritional status is widely reported to be associated with improved systemic immune function and better prognosis [27,28]. Stoma formation is also a great threat to QOL for LRC patients due to the low acceptance rate, troublesome stoma nursing, and psychological burden.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative nutritional evaluation and support by ERAS nursing program can reduce the incidence of insulin resistance and postoperative hyperglycemia, and reduce preoperative anxiety. The improvement of nutritional status is widely reported to be associated with improved systemic immune function and better prognosis [27,28]. Stoma formation is also a great threat to QOL for LRC patients due to the low acceptance rate, troublesome stoma nursing, and psychological burden.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative nutritional evaluation and support by ERAS nursing can reduce the incidence of insulin resistance and postoperative hyperglycemia, and reduce preoperative anxiety. The improvement of nutritional status is widely reported to be associated with improved systemic immune function and better prognosis (27,28). Stoma formation is also a great threat to QOL for LRC patients due to the low acceptance rate, troublesome stoma nursing, and psychological burden.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that in ammation is related to the occurrence, development and metastasis of malignant tumors [7][8][9][10][11]. Because the leukocyte count and various types of white blood cells are indicators of systemic in ammation and immune response, these values may be good candidate biomarkers for predicting aggressive tumors.…”
Section: Discussionmentioning
confidence: 99%